2020
DOI: 10.1088/1361-6528/ab72bd
|View full text |Cite
|
Sign up to set email alerts
|

A high-performance triboelectric nanogenerator with improved output stability by construction of biomimetic superhydrophobic nanoporous fibers

Abstract: The utilization of nanoporous materials is an extremely effective approach to enhance the electrical performance of triboelectric nanogenerators (TENGs). However, existing methods for preparing nanoporous tribo-materials are not only complicated, costly and time-consuming, but also waste a lot of material. Meanwhile, fabricated nanoporous tribo-materials that have low roughness by nature possess poor surface hydrophobicity, causing low output stability in humid environments. Here, a bio-inspired petiole-like m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 61 publications
0
38
0
Order By: Relevance
“…This is consistent with the conclusion of Zhang et al's work. [ 11 ] Furthermore, Zhang et al pointed out that the filamentous structure of PVDF membrane prepared with high‐concentration spinning solution contains a large number of nanopores inside and on the surface. Nanopores act as charge traps that can hold more charges on the surface of the membrane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the conclusion of Zhang et al's work. [ 11 ] Furthermore, Zhang et al pointed out that the filamentous structure of PVDF membrane prepared with high‐concentration spinning solution contains a large number of nanopores inside and on the surface. Nanopores act as charge traps that can hold more charges on the surface of the membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Electrospinning can effectively avoid the aforementioned disadvantages, but the method is limited by materials. [ 11 ] It is necessary to find new directions to improve the power generation performance of TEG. As for integration and application of TEG, Qin et al .…”
Section: Introductionmentioning
confidence: 99%
“…• Electrospinning: Electrospinning can quickly produce nanofibers from a wide range of materials in a continuous manner and has been used for fabricating triboelectric layers with high specific surface areas, and porosities. 36,86,[139][140][141] Cheon et al 86 reported a highperformance TENG using the electrospun polyvinylidene fluoride-silver NWs (PVDF-AgNWs) and nylon nanofibers with high specific surface areas, which functioned as the negative and positive triboelectric materials, respectively ( Figure 3F). The authors found that the addition of AgNWs enhanced the trapping of triboelectric charges and the surface charge potential in PVDF, both of which contribute to the observed significant enhancement in the output performances of the electrospun TENG device.…”
Section: Porous Sponge Structurementioning
confidence: 99%
“…The content of DI water could adjust the porosity in the mixture. This work provides a more environmentally friendly way to achieve the porous sponge structure but suffers from the poorer controllability of the porosity than the methods using controlled sacrificial templates such as the PS spheres. Electrospinning : Electrospinning can quickly produce nanofibers from a wide range of materials in a continuous manner and has been used for fabricating triboelectric layers with high specific surface areas, and porosities 36,86,139‐141 . Cheon et al 86 reported a high‐performance TENG using the electrospun polyvinylidene fluoride‐silver NWs (PVDF‐AgNWs) and nylon nanofibers with high specific surface areas, which functioned as the negative and positive triboelectric materials, respectively (Figure 3F).…”
Section: Materials Engineering For Tengs With Improved Performancementioning
confidence: 99%
“…However, such electromagnetic generators are heavy, bulky, and immovable and are generally situated near dams, coasts, or river banks. [ 3–5 ] Furthermore, generating electricity using a traditional electromagnetic apparatus is difficult under low water supply, such as rainwater or fog. [ 6 ] Therefore, a small, novel, and portable electromagnetic system that can harvest energy from tiny water drops can act as a water‐electricity transducer; such a system is an alternative to traditional hydropower equipment.…”
Section: Figurementioning
confidence: 99%